Metode Certainty Factor dalam Mengidentifikasi Gangguan Koneksi Internet pada Metro Ethernet - Sepdi Armet (SEULANGA SYSTEM PUBLISHER, 2023)
In an effort to support the IT-based government service program, better known as e-Government, the Pariaman City Government has built a metro ethernet network. Metro ethernet Kota Pariaman is a metro area network that functions as a means of internet access for all Regional Apparatus Organizations (OPD) throughout Kota Pariaman. Disruption to internet access will have an impact on Pariaman City Government services to the community, such as delays in health administration services using an online system. Lack of understanding of computer users in dealing with internet network problems, this requires the role of experts to identify damage to the metro ethernet network. The development of the Expert System aims to assist computer users or network technicians in identifying metro ethernet network disturbances and providing solutions to correct these disturbances. The Expert System was developed based on the existing problems, where for data collection interviews and field observations were carried out. The method used for data processing in this expert system is the certainty factor method. The certainty factor method can define the certainty of a fact that allows an expert to describe the beliefs of the problems at hand. Based on the results of expert system testing using certainty factors to identify internet connection problems, it produces information that causes disturbances with an accuracy rate of 90.2% of the average certainty factor value. Based on the results obtained by the Expert System with the certainty factor method, it can be used to identify internet connection problems on the Pariaman City metro ethernet network.